Protective Effects of Montelukast Against Stress-Induced Degeneration of the Urinary Bladder - ERCAN, FERİHA; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (MARMARA UNIV, INST HEALTH SCIENCES, 2018)
Objective: The aim of the study was to investigate the role of montelukast (ML), a cysteinyl leukotriene-1 receptor antagonist, on the water avoidance stress (WAS) - induced degeneration of the rat urinary bladder mucosa. Methods: In WAS group, rats were exposed to WAS two hours daily for five days. In WAS+ML group, rats were administered ML (10 mg/kg; i.p.;) following every WAS exposure for 5 days. In control group, rats were injected vehicle solution only. The urinary bladder was evaluated for general morphology at light microscope. Mast cell activation and uroplakin distribution were assessed with immunohistochemistry. Glycosaminoglycan (GAG) distribution and urothelial permeability were observed using ruthenium red (RR) staining techniques in transmission electron microscope and luminal urothelial cells were observed with scanning electron microscope. Tissue malondialdehyde (MDA) and gluthatione (GSH) levels were also analysed. Results: Irregular GAG layer and uroplakin distribution, penetration of RR in the intercellular spaces and dilated tight junctions in urothelial layer, increase in inflammatory cell infiltration, in number of both granulated and activated mast cells, and were observed in the WAS group. The MDA level was increased, and GSH level was decreased significantly in urinary bladder in the WAS group in comparison with the control group. Quite regular GAG layer, uroplakin distribution and tight junctions in most regions, decrease in inflammatory cell infiltration and both of activated and granulated mast cells in the mucosa, were observed in WAS+ML group. Moreover, significant decrease in MDA and increase in GSH levels were observed in this group. Conclusion: Montelukast appears to exert a protective activity in WAS induced urinary bladder injury by inhibiting inflammatory and oxidative activity.
Keywords: Water avoidance stress; montelukast; urinary bladder; uroplakin; mast cell; INTERSTITIAL CYSTITIS; RECEPTOR ANTAGONIST; MAST-CELLS; LEUKOTRIENES; PERMEABILITY; UROTHELIUM; ASTHMA; INJURY